Surveillance, Governmentality and moving the goalposts: The influence of Ofsted on the work of schools in a post-panoptic era. Issue 2 (3rd April 2018) - Perryman, Jane; Maguire, Meg; Braun, Annette; Ball, Stephen
ABSTRACT: This paper asks the question: to what extent do inspection regimes, particularly the Office for Standards in Education (Ofsted), influence the work of a school, and how might that influence be conceptualised? It draws on an ESRC-funded study of 'policy enactments in secondary schools', which was based on case-study work in four 'ordinary' schools. Here the data set is re-examined to understand the extent to which Ofsted had an ongoing influence on the work of the leadership, management and teachers in these schools. We undertook a process of secondary analysis of the data from the project and found that the influence of the inspection agenda was strong in the schools, policy decisions were often being made to conform to Ofsted's expectations and the influence on leadership and management was clearly apparent. In resisting this agenda we also found that schools to some extent performed 'the good school' for inspections. Finally, we relate this empirical evidence to conceptions of governmentality and post-panopticism to shed new light on their theoretical relevance to contemporary inspection regimes.